Hierarchy and structure of love attitudes of Belarusians and Chinese - Fourmanov, Igor A.; Nie, Xinchun; Zhao, Xiaoxuan (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
It was found that in the hierarchy of love attitudes of Belarusian men and women, the dominant position is occupied by Eros, Agape and Mania, in Chinese men – Agape, Pragma and Eros, in Chinese women – Agape, Pragma and Mania. Regardless of nationality and gender, Ludus takes the last place in the hierarchy of love attitudes. The regression analysis identified five types of lovers: emotional, rational, devoted, anxious, and playful.